Failure mechanisms in carbon fiber reinforced plastics (CFRP) / aluminum (Al) adhesive bonds subjected to low-velocity transverse pre-impact following by axial post-tension. (1st September 2019) - Liu, Xinglong; Shao, Xuefei; Li, Qing; Sun, Guangyong
Abstract: The present study aimed to explore the effects of impact surface and impact energy on the residual characteristics of the carbon fiber reinforced plastics (CFRP)/aluminum (Al) adhesive bonded joints. The adhesive specimens were manufactured in the hot pressing machine with specific curing temperature and curing pressure of the adhesive. In the experiments, a transverse low velocity pre-impact was carried out first and then followed by the axial (longitudinal) tensile test. The results divulged that CFRP, as an impact surface, could generate better structural integrity and decrease loss of joint strength in comparison with the aluminum impact surface. The mechanism for alternating residual tensile strength resulting from transverse impact load was the combined effect of both damage and mechanical interlocking effectiveness. The residual tensile strength and failure displacement decreased with increasing impact energy except for the joint strength impacted onto the aluminum surface at 10 J due to the prominent mechanical interlocking effect. The strain evolution paths in the adherends at the overlap region presented the different forms when impacted onto the different surfaces. In the tensile tests, the fracture surfaces for the joints with impacting on the aluminum surface can be classified as shear failure zone, annular failure zone and mixed failure zone, while the fracture surfaces for the joints with impacting onto the CFRP surface classified to be shear failure zone and crossed impact zone. This study is expected to provide systematic understanding on crashing behavior of adhesive joints with dissimilar materials for multiple impacts from different directions.